Wpływ eksplantatu inicjalnego na efektywność transformacji Gerbera hybrida za pomocą Agrobacterium tumefaciens - Nowak, Elżbieta; Rojek, Żaneta; Kucharska, Danuta; Orlikowska, Teresa (Committee on Biotechnology PAS, 1997)
An efficient method for genetic Agrobacterium tumejaciens-mediated transformation of fivecultivars Gerbera hybrida was established. The youngest leaves and shoot tips from proliferatingin vitro cultures were co-cultivated with disarmed strain LBA 4404/pBI121 carrying the chimaericgenes nptll and gus. The inoculated explants were repeatedly cultured on regeneration mediumwith kanamycin and Biotaksym. After 9-10 months from 0.04 to 0.25 independently transformedshoots from one inoculated leaf and from 0.06 to 0.65 from one inoculated shoot tip wereobtained, depending on cultivar and additional treatment. Transformed shoots accounted for 5.0to 50.0% of all regenerated shoots. Additional wounding of leaves before inoculation by squeezingand scratching off increased transformation efficiency. Better results for recalcitrant to regeneration cultivars were obtained if squeezed shoot tips were inoculated. Regenerating shoots wereselected on kanamycin, screened for gas expression with X-gluc and tested by PCR for nptlland gus genes. All together 162 transgenic shoots were obtained in cvs Amber, Boy, Ferrari,Mariola and Tamara, but only 24 relatively stable lines were established.
Keywords: biotechnology